Clinical and morphological features of gastroduodenal pathology at alcohol-induced liver disease - I. V. Kozlova; M. A. Suschenko (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine clinical and morphological features and mechanisms of development of gastroduodenal lesions at alcohol-induced disease of liver.Material and methods. Overall 137 patients with alcoholic disease of the liver were investigated. Clinical, endoscopic, morphological, immunehistochemical diagnostic methods were applied.Results. Clinical, endoscopic and morphological features of gastroduodenal mucosa lesions in patients with alcohol-induced disease of the liver were revealed. Increase of morphometrical parameters of epithelial cells of stomach mucosa, immunepositive to nitric oxide synthase, endothelin-1, melatonin and glucagon, decrease of proliferative activity and increase of apoptosis of epithelial cells of stomach mucosa was found.Conclusion. Pattern of gastroduodenal lesions in many respects is determined by clinical and morphological variant of liver diseases, as well as by equivocal changes of diffuse endocrine system components and proliferative activity of stomach mucosa epithelial cells.